2013
DOI: 10.3201/eid1912.130701
|View full text |Cite
|
Sign up to set email alerts
|

Lack of MERS Coronavirus Neutralizing Antibodies in Humans, Eastern Province, Saudi Arabia

Abstract: We used a lentiviral vector bearing the viral spike protein to detect neutralizing antibodies against Middle East respiratory syndrome coronavirus (MERS-CoV) in persons from the Eastern Province of Saudi Arabia. None of the 268 samples tested displayed neutralizing activity, which suggests that MERS-CoV infections in humans are infrequent in this province.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 9 publications
(8 reference statements)
2
34
0
1
Order By: Relevance
“…In three earlier cross-sectional serologic studies, none of the 3024 participants showed evidence of previous infection with MERS-CoV. 1,14,15 In our study, the detection of antibodies was most likely due to our focus on household contacts of index patients. Differences in assay sensitivity may play an additional role.…”
Section: Discussionmentioning
confidence: 67%
“…In three earlier cross-sectional serologic studies, none of the 3024 participants showed evidence of previous infection with MERS-CoV. 1,14,15 In our study, the detection of antibodies was most likely due to our focus on household contacts of index patients. Differences in assay sensitivity may play an additional role.…”
Section: Discussionmentioning
confidence: 67%
“…The cIFA in this study produced a significant number of false positives that required exclusion by confirmatory neutralization assay (Aburizaiza et al, 2013). Another study conducted in Saudi Arabia made use of MERS-S pseudotyped lentiviruses to test for virus-neutralizing antibodies (Gierer et al, 2013b). HCoV-NL63 S pseudotyped viruses were used as controls.…”
Section: Diagnostics For Newly Emerged Mers-covmentioning
confidence: 99%
“…MERS-CoV enfeksiyonu yaşlı-larda ve altta yatan başka hastalığı olanlarda daha ağır klinik seyir ve ölüme yol açmaktadır (1) . Suudi Arabistan'da yürütülen serolojik çalışmalarda MERS-CoV antikorlarının prevalansı düşüktür (39,40) . Suudi Arabistanlı genel popülasyonu temsil eden (10.009 kişi) bir çalışmada, seropozitiflik oranı genel popülas-yonda %0,15, deve çobanları ve kesimevi çalışanlarında %3,1 bulunmuştur (41) .…”
Section: Mers-cov Için Başlıca Hayvan Ara Konağın Arapunclassified